2011
DOI: 10.3109/1547691x.2010.543095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suppressive effects of paraquat on innate immunity in Balb/c mice

Abstract: The toxic effect of paraquat (PQ), an herbicide that has been used widely in agriculture, on some parameters of the immune system was investigated. PQ was administered to Balb/c mice as intraperitoneal doses of 0.01, 0.1, or 1.0 mg PQ/kg body weight (BW) for a total of 28 days. Besides the histopathological examination of each host?s vital organs, measures of their splenic and bone marrow cellularity, blood macrophage/granulocyte phagocytic activity, total serum immunoglobulin M (IgM) and IgG, complement C3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The amount (μL) of each serum causing 50% hemolysis (K) was determined by plotting (on log–log graph paper) serum volume in μL added ( x ) versus [ y /(1 − y )]; this plot is expected to be linear. At 50% hemolysis, y /1 – y = 1; hence, the intercept on the x ‐axis from this point corresponds to 1 CH 50 unit for that sample of serum …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount (μL) of each serum causing 50% hemolysis (K) was determined by plotting (on log–log graph paper) serum volume in μL added ( x ) versus [ y /(1 − y )]; this plot is expected to be linear. At 50% hemolysis, y /1 – y = 1; hence, the intercept on the x ‐axis from this point corresponds to 1 CH 50 unit for that sample of serum …”
Section: Methodsmentioning
confidence: 99%
“…In each case, a minimum of 100 000 events was analyzed per sample. Ultimately, each presenting cell value was expressed as fluorescence intensity/phagocytic cell …”
Section: Methodsmentioning
confidence: 99%
“…Complements have been involved in early immune reaction but complement component 3 (C3) levels in serum were not altered with long-term PQ exposure in Balb/c mice (29). Sun et al (30) demonstrated that blocking the complement pathway ameliorates acute lung injury (ALI) induced by PQ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of the immune system induces significant changes in the human body. Immune-suppression has been shown to be caused by various external stresses, including pesticides, alcohol and tobacco abuse, antibiotics, chemotherapy, birth control pills, cortisone, and other drug therapies [4,5,6]. Recently, herbal extracts have been studied extensively for their potential therapeutic effects in immune function.…”
Section: Introductionmentioning
confidence: 99%